Parents' perspectives on home-based character education activities. Issue 3 (3rd July 2022) - Paul, Shirley-Anne S.; Hart, Peter; Augustin, Limor; Clarke, Paula J.; Pike, Mark
ABSTRACT: This study investigated parents' perspectives on a taught character education programme implemented with children in their schools and homes. Semi-structured interviews were conducted with forty-one parents of secondary school students participating in the Narnian Virtues Character Education English Project. Parents answered questions relating to the curriculum's home activities which they undertook with their child. A thematic analysis of the data revealed five main themes: mechanics of the project; influence on family life and parenting; influence on children's character development; self-reflective nature of the project; and parent's views on character development. The results suggest that the curriculum positively influences students' character development and is effective for involving parents in their child's character education. The findings have significance for academics, practitioners, and policymakers looking to engage parents as partners in character education programmes.